Model Kamar Parlemen (Catatan untuk Penataan Kelembagaan DPD Indonesia) - Isra, Saldi (FH Universitas Muhammadiyah Yogyakarta, 2007)
Indonesia has just amended their constitution for the fourth times; One of the most important progresses is the existence two chambers in parliament chambers, DPR and DPD. But it still has a huge debatable up until now, especially about type of chamber in Indonesian parliament. Even though some experts says that Indonesia has bicameralism, but another experts say that Indonesia has tricameralism with DPR, DPD and MPR. This article will tray to portray the models of chamber in parliament which is ever used in the whole world. And this article found that there are four types of chamber in parliament; unicameralism, bicameralism, tricameralism and tetracameralism. All of these types have their own advantages and disadvantages. At least, this article will portray which one from the types of chamber is the best for Indonesian condition. This article says that it has to have relation to Indonesian needs and the truth function of parliament body in Indonesian constitutionalism.